EVALUATION OF TOLERANCE OF 88 F1 CORN GENOTYPES IN ACIDIC DRY SOIL STRESS IN MONCONGLOE, MAROS BASED ON MORPHOPHYSIOLOGICAL MARKERS - Muhammad Rifki Aulia; Rusnadi Padjung; Muhammad Azrai (Gunung Djati Conference Series, 2026)
This research was conducted at the Hasanuddin University experimental farm, Moncongloe District, Maros Regency, South Sulawesi with two main objectives: (1) to determine the effect of acidic dry soil stress on genetic diversity and heritability values ​​of agronomic traits of corn plants and (2) to characterize candidate hybrids tolerant to acidic dry soil stress based on the production response of corn genotypes .Method: this study used 88 genotypes with a randomized block design adopted as an experimental design. The parameters in this study were: soil chemical properties, observation of plant characteristics, and analysis of stress tolerance index. Based on the results of this study, it can be concluded that: (1) dry acidic soil stress has an effect on the phenotype and low to moderate values ​​on the heritability of plants with the characters of 10 cob weight, cob length, and productivity having relatively higher values ​​than other characters. (2) Genotypes G62 and G86 occupy the intersection between high yields under optimum conditions (Yp), high yields on acid soils (Ys), and high STI values. Both genotypes are capable of maintaining high yields, namely 8.8–9.0 t ha⁻¹ at optimum conditions and 7.5 t ha⁻1 on acid soils. These characteristics reflect the ideal profile in breeding corn tolerant to acid soils.